Sosialisasi Pencegahan dan Pengendalian Demam Berdarah Dengue (DBD) di RT 001, Kelurahan Karingau, Kecamatan Balikpapan Barat - Kisanjani, Alex; Lambi, Adi Bin Paulus; Rahman, Nadya Novia; Nurdin, Ishak (LPPM UMRI, 2023)
The spread of Dengue Hemorrhagic Fever (DHF) is very fast, especially in countries with tropical climates such us Indonesia. This is because high rainfall makes it easier for the Aedes aegypti mosquito to breed and continue its life cycle. DHF is an acute febrile disease caused by a virus infection. According to the World Health Organization, Indonesia is the country with the highest cases of dengue fever in Southeast Asia. Based on data in June 2022, there were 45.000 cases of dengue fever and the number increased in July 2022 to 52.000 cases of dengue fever. The aim of carrying out this PkM activity is to increase the knowledge of the Kariangau Village community in efforts to prevent and control dengue fever. The method used is socialization of ways to prevent and control dengue fever. This activity was carried out on August 12, 2023 at Posyandu RT 001 Kariangau Village and involved the local community.